China’s fiscal expenditure on agriculture: Impact on the urban–rural income gap - Mao, Rui; Ruan, Maoqi; Shi, Xinjie; Sun, Weiqi; Chen, Kevin Z. (2022)
Since the reform and opening-up in 1978, China’s income distribution gap has widened. The Gini coefficient of national residents’ income rose from 0.31 in 1981 to a historic high of 0.49 in 2008 and has continued to hover at a high of 0.46 in the recent years (Molero-Simarro, 2017; Li and Zhu, 2018; Luo et al., 2021). Narrowing the income gap between urban and rural residents is the key to reducing China’s Gini coefficient. The ratio of per capita income between urban and rural residents exhibited an overall growth trend before 2009, despite the increase in disposable income per capita of rural residents from 134 yuan in 1978 to 18,931 yuan in 2021. In 2007, the urban–rural income ratio exceeded 3:1 for the first time and contributed over 50% to the Gini coefficient of the national income distribution (Li and Wan, 2013). Since 2009, the urban–rural income gap has decreased; however, the decline has nearly halted post 2014. In 2021, the urban–rural income ratio was still as high as 2.5:1, almost equal to that in 1978 and larger than that in developed countries, which have a level of approximately 1:1 or lower.